Accounting treatment of fixed assets and application of the depreciation method at PT Makmur Bintang Plastindo Medan - Khairunisa Hanum; Arnida Wahyuni Lubis (Institute of Computer Science (IOCS), 2023)
Decision makers heavily rely on Fixed Assets accounting as an information tool. The company's management policy determines various methods of acquiring fixed assets, each of which affects the acquisition price. Depreciation, also known as the systematic allocation of the depreciable amount of an asset over its useful life, can be performed using various methods such as straight-line, units of production, and declining balance. The purpose of this study was to assess whether PT Makmur Bintang Plastindo Medan's accounting treatment for fixed assets and the depreciation method comply with Statement of Financial Accounting Standards (PSAK) No. 16. The research methodology used was descriptive qualitative. The findings show that PT Makmur Bintang Plastindo Medan applies accounting practices for its fixed assets in accordance with PSAK No. 16. PT Makmur Bintang Plastindo categorizes fixed assets based on their useful lives and acquires them through cash purchases, credit purchases, and joint purchases, in accordance with PSAK No. 16. Maintenance and repair costs are recorded as expenses in maintaining fixed assets at PT Makmur Bintang Plastindo. The company disposes of fixed assets through sale, destruction, or gifting, and presents them on the balance sheet at book value, which is the acquisition cost minus accumulated depreciation. PT Makmur Bintang Plastindo accurately presents its fixed assets in accordance with PSAK No. 16. Furthermore, PT Makmur Bintang Plastindo uses the straight-line method for depreciating its fixed assets, resulting in consistent annual depreciation charges. This method is considered easy to implement and understand.